2008
DOI: 10.1097/npt.0b013e3181660f0c
|View full text |Cite
|
Sign up to set email alerts
|

Altered Trunk Position Sense and Its Relation to Balance Functions in People Post-Stroke

Abstract: Subjects with poststroke hemiparesis exhibit greater trunk repositioning error than age-matched controls. Trunk position sense retraining, emphasizing sagittal and transverse movements, should be further investigated as a potential poststroke intervention strategy to improve trunk balance and control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
144
0
23

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 194 publications
(169 citation statements)
references
References 43 publications
2
144
0
23
Order By: Relevance
“…This task-oriented proprioception training may have caused the improvement. Ryerson et al (2008) reported a significantly higher Values are expressed as mean ± Standard deviation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This task-oriented proprioception training may have caused the improvement. Ryerson et al (2008) reported a significantly higher Values are expressed as mean ± Standard deviation.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Verheyden et al (2009) showed that 10 hours of additional trunk exercises improved the ability to control the trunk in subacute stroke patients, and reaching exercises performed while seated were reported to improve sitting balance, peak vertical force on the paretic foot, and gait speed in chronic hemiplegic patients (Dean et al 2007). Ryerson et al (2008) stated that proprioceptive training is essential to improve trunk control and balance, and Eils and Rosenbaum (2001) suggested that exercising on an unstable surface is effective in improving body position awareness. One study reported that trunk exercises on a physio ball are effective in improving trunk control and functional balance in acute stroke patients (Karthikbabu et al 2011a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…대부분의 편마비 환자는 자세조절에 어려움을 겪게 되는데 그 중 체간은 신체의 중심으로서 기능적 움직임시의 자세를 조정해 중 력에 대항하고 사지의 움직임을 준비하며 동적 움직임시 의 중심이동을 조절하여 새로운 자세로의 적응을 할 수 있도록 돕는다 [6]. 체간의 강한 안정성은 균형과 사지의 움직임에 필수적이며 상지와 하지의 능숙한 사용은 숙련 된 기술과 일상생활 동작의 필수조건이다 [7]. 체간근력은 균형 능력과 기능적 활동에 관련이 있는데, 체간근력이 약한 편마비 환자는 균형 능력이 부족하고, 기능 활동의 수행에 어려움이 있다 [8].…”
unclassified